Racismo ambiental e direito à cidade: desafios diante das mudanças climáticas - Sousa, Bárbara Dantas de (2024)
This dissertation investigates the interrelations between environmental racism, the right to the city, and climate change in the Brazilian urban context, exploring how these dynamics contribute to perpetuating socio-spatial inequalities and compromising environmental justice. The study adopts a qualitative approach, combining Systematic Literature Review (SLR) and documentary analysis grounded in discourse analysis, to understand how normative frameworks and policy guidelines can be leveraged to build more just and inclusive cities. The findings highlight that environmental racism disproportionately exposes peripheral populations, especially Black communities, to climate risks, while public policies face limitations due to structural barriers. It concludes that the right to the city, as a normative principle, holds transformative potential to address inequalities, but its realization depends on integrated policies and effective citizen participation. This research contributes to urban studies by proposing pathways for building more resilient, inclusive cities aligned with SDG 11.